1866 Utah Acts 59, ch. 22, tit. 8, § 102 - (:unkn) unknown (My University, 1865)
Prohibited the "set[ting] of any gun." Punishable by imprisonment of up to 1 year or a fine of up to $500.
Keywords: TRAP GUNS